1997
DOI: 10.1055/s-2006-957657
|View full text |Cite
|
Sign up to set email alerts
|

Complement-Modulating Properties of a Kaempferol 7-O-Rhamnosylsophoroside from the Leaves ofMorinda morindoides

Abstract: A kaempferol 7-O-rhamnosylsophoroside isolated from the leaves of Morinda morindoides showed dose-dependent complement-modulating properties towards both the classical (inhibiting effect) and alternative (activating effect) pathways of the complement system. Its structure was elucidated by chemical and spectroscopic methods as kaempferol 7-O-[alpha-L-rhamnopyranosyl-(1-->6)]-[beta-D-glucopyranosyl-(1-->2)]-be ta-D-glucopyranoside, a new natural product which was named morindaoside.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
14
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 6 publications
5
14
0
Order By: Relevance
“…The signal at δ 81.1 attributable to C-2' of primary glucose indicated glucopyranosyl (12)-glucopyranosyl arrangement (as in sophorosyl) while that at δ 67.9 attributed to C-6' of the same glucose signified rhamnopyranosyl-(16)-glucopyranosyl moiety (as in rutinosyl). 21 The 13 C NMR data for the trisaccharide were in agreement with [α-rhamnopyranosyl-(1'''6')][β-glucopyranosyl-(1''2')]-glucopyranosyl moiety. 21,22 Thus, based on the above spectroscopic evidences, compound 3 was deduced to be 16α,22α,28-trihydroxyolean-12-ene- 1 H NMR (seven methyl proton singlets and a broad triplet vinyl proton at  5.36), suggested that the aglycone possessed an olean-12-ene skeleton with an aldehyde group.…”
supporting
confidence: 57%
See 2 more Smart Citations
“…The signal at δ 81.1 attributable to C-2' of primary glucose indicated glucopyranosyl (12)-glucopyranosyl arrangement (as in sophorosyl) while that at δ 67.9 attributed to C-6' of the same glucose signified rhamnopyranosyl-(16)-glucopyranosyl moiety (as in rutinosyl). 21 The 13 C NMR data for the trisaccharide were in agreement with [α-rhamnopyranosyl-(1'''6')][β-glucopyranosyl-(1''2')]-glucopyranosyl moiety. 21,22 Thus, based on the above spectroscopic evidences, compound 3 was deduced to be 16α,22α,28-trihydroxyolean-12-ene- 1 H NMR (seven methyl proton singlets and a broad triplet vinyl proton at  5.36), suggested that the aglycone possessed an olean-12-ene skeleton with an aldehyde group.…”
supporting
confidence: 57%
“…21 The 13 C NMR data for the trisaccharide were in agreement with [α-rhamnopyranosyl-(1'''6')][β-glucopyranosyl-(1''2')]-glucopyranosyl moiety. 21,22 Thus, based on the above spectroscopic evidences, compound 3 was deduced to be 16α,22α,28-trihydroxyolean-12-ene- 1 H NMR (seven methyl proton singlets and a broad triplet vinyl proton at  5.36), suggested that the aglycone possessed an olean-12-ene skeleton with an aldehyde group. 19 The combined interpretation of 1 H and 13 C NMR aided by HSQC allowed association of most protons with the corresponding carbon signals, and by the HMBC spectrum, which was vital in connecting the various spin systems, the aglycone was suggested to be 3β, 22α-dihydroxyolean -12-en-28-al , a fact corroborated by the EIMS peaks at m/z 514.2.…”
supporting
confidence: 57%
See 1 more Smart Citation
“…The complement system is recognized as an important pathway of host defence against infection, as well as mediating immunological and inflammatory reactions. 28) As shown in Fig. 2, the sterol fraction (8.8-140 mg/ml) inhibited the haemolitic activity of the classical complement pathway (IC 50 : 35.5 mg/ml, standard conditions).…”
Section: Resultsmentioning
confidence: 70%
“…An aqueous decoction of fresh leaves, which is the typical traditional remedy is used for the treatment of various illnesses among which the diarrhoea and constipation associated with intestinal worms (Kambu, 1990;Newinger, 2000). While the literature data point out the presence of saponins, flavonoids, terpenes, steroids, tannins and anthraquinones, the absence of anthocyanes and the doubtful presence of alkaloids in Morinda morindoides leaves (Kambu, 1990), extensive phytochemical studies on this medicinal plant part have led to the isolation and structure elucidation of flavonoids (Cimanga et al, 1995a(Cimanga et al, , 1997, iridoids (Cimanga et al, 2003) and anthraquinones (Cimanga et al, 2008). Some interesting biological activities related to some of its traditional uses including the in vitro and in vivo antimalarial (Onabanjo, 1983;Cimanga et al, 2008), the in vitro anticomplementary (Cimanga et al, 1995b(Cimanga et al, , 1997(Cimanga et al, , 2003, antioxidative ), cardioinhibitory (N'Guessan et al, 2002, antiamoebic (Cimanga et al, 2006) and immunologic (Mankele et al, 2006) activities, were previously reported.…”
Section: Introductionmentioning
confidence: 99%